Dúvidas e dívidas : a reforma agrária de mercado em Lagarto-SE - Souza Júnior, Benizário Correia de (2012)
In the last three decades, many studies in the social sciences were marked by an intense discussion, focusing on the problems of the field. Conflictual relations with the peasantry grabbers and landowners, as well as the discussion on decomposition or recreating the peasantry class and the way in which this fits into the capitalist market, has been the focus of those discussions. Historically, the Brazilian rural space is conceived as a stage of intense social conflicts, as the main reason the possession and ownership of land. Such conflicts are aimed at a better distribution of land and the promotion of a fair land reform, which, thus, promotes a better distribution of income and consequently fewer social injustices. However, the current landscape of agrarian conflicts are marked by new model of agrarian policy, known as market land reform, based on a land market, idealized by BIRD (Brazilian acronym for World Bank) and promoted and improved by the Brazilian state. In Sergipe, the agrarian problem is exacerbated due to the small land area of the state, which creates a social pressure, aggravating the direct conflicts over land ownership. And it is from the perspective of solving such problems that the agrarian reform Market (RAM as Brazilian acronym), as it is known, is now sold in Sergipe, as well as in every state that has adopted the policy of agrarian reform. In the field of geography, this phenomenon gains a prominent position, since this new form of management of the Brazilian space promotes a brand new territorial dynamics of these spaces. Thus requiring a deeper analysis of the related, multi-dimensional, multi-scale and timeless processes that determine not only new territory, but the peculiar form that territoriality shape them, from a previously recorded identity and experiences in the territories of the past. In Sergipe, such a model of agrarian reform began to be implemented in 2001 with the Fund for Land and Agrarian Reform (then the Land Bank program) and continued with the National Land Credit Program in both lines of credit, CAF and PCPR. In our study, we analyzed both lines using as spatial area the town of Lagarto, and we found that: the ideals of agrarian reform came to be disguised by the policies of RAM; agrarian reform proposed by BIRD had no significant changes in the reality of the beneficiaries; RAM as a public policy of poverty reduction will act as a tool for redefining the territorial dynamics of the spaces where it‟s located; the absence of pubic power in the enterprises of RAM favors the creation of an illegal land market, since the lack of a close up leaves openings for marketing of lots; RAM is incorporated in the implementation of neo-liberal state and it is used as an instrument for perpetuating accumulation of capital, as well as social repression, denying the struggle as an instrument of social transformation and undermining social movements from the discourse of passivity. Against all the odds, good data was found in the territories surveyed. Stands out in this scenario a sense of satisfaction, which assigns the symbolic realization of an identity projected in the fieldwork. In this sense, the appropriation of land by peasant is characterized not by their material relations but by the symbolic value that it has for their way of life and work.